2015
DOI: 10.7860/jcdr/2015/13173.6049
|View full text |Cite
|
Sign up to set email alerts
|

A Nonsyndromic Autosomal Dominant Oligodontia with A Novel Mutation of P AX 9 -A Clinical and Genetic Report

Abstract: An 8-year-old female patient (proband) reported to the Department of Paediatric Dentistry with a chief complaint of multiple decayed teeth in lower left quadrant of the jaw. The patients past medical history and the family history were not significant. It was patient's first visit to a dentist. Extra-oral examination revealed no abnormalities. Intraoral examination, revealed grossly decayed teeth in relation to 54, 65, 74 and hypo plastic teeth in relation to 64 and 84. The proband (III: 9) Orthopantomographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This might be taken as an indication that the mutation is causative, but an association study with much larger cohort would be needed before more positive conclusions are made. Thimmegowda et al published a case report for the Ille25Ille mutation but it was not entirely clear which family members were/were not the carriers. The precise locus of the mutation was not given and the corresponding protein structure was not included so the putative impact—if there is any—on hypodontia is hard to evaluate.…”
Section: Mutations and Polymorphisms In The Pax9 Genementioning
confidence: 99%
“…This might be taken as an indication that the mutation is causative, but an association study with much larger cohort would be needed before more positive conclusions are made. Thimmegowda et al published a case report for the Ille25Ille mutation but it was not entirely clear which family members were/were not the carriers. The precise locus of the mutation was not given and the corresponding protein structure was not included so the putative impact—if there is any—on hypodontia is hard to evaluate.…”
Section: Mutations and Polymorphisms In The Pax9 Genementioning
confidence: 99%
“…The heterozygous missense PAX9 variant, c.59C>T (p.Pro20Leu), was observed in Family 1 with four affected members. The p.Pro20Leu was previously reported in two nonsyndromic tooth agenesis families, an Indian family with four affected members [29] and a Japanese family with three affected members [30] (Table 2). In total, there were eight cases identified with the p.Pro20Leu having definite records of third molars.…”
Section: Discussionmentioning
confidence: 78%
“…Although identical mutation was previously reported in an Indian family with tooth agenesis, since experimental evidences for its causality is lacking [15,16], we decided to investigate this mutation in detail. The variant allele was shared exclusively by the three familial patients as heterozygotes, and not by an unaffected member of the family (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro experiment confirmed the detrimental effect of the mutation on PAX9 activity as a transcription factor. Thimmegowda et al recently reported a haplotype containing both c.59C>T and c.75C>T mutations in the PAX9 coding region in an Indian family with tooth agenesis, which would result in P20L and silent mutation at Ile25 [15,16]. However, they did not refer to the resulting amino acid change, co-segregation of the variant within the family, or the functional implications of the variant.…”
Section: Introductionmentioning
confidence: 99%